MARKETING TOOLS IN THE MANAGEMENT OF THE DEVELOPMENT OF A GENERAL EDUCATION ORGANIZATION (World Bulletin of Management and Law, 2023)
This article discusses marketing tools in the management of a general education institution to ensure competitiveness in the market of educational services.
Keywords: education; institution; marketing; management